Examination of WHO/INRUD Core Drug Use Indicators at Public Primary Healthcare Centers in Kisii County, Kenya - Aggrey O. Nyabuti; Faith A. Okalebo; Eric M. Guantai (Hindawi Limited, 2020)
Background. Irrational drug use is a global problem. However, the extent of the problem is higher in low-income countries. This study sets out to assess and characterize drug use at the public primary healthcare centers (PPHCCs) in a rural county in Kenya, using the World Health Organization/International Network for the Rational Use of Drugs (WHO/INRUD) core drug use indicators methodology. Methods. Ten PPHCCs were randomly selected. From each PPHCC, ninety prescriptions from October to December 2018 were sampled and data extracted. Three hundred (30 per PPHCC) patients and ten (1 per PPHCC) dispensers were also observed and interviewed. The WHO/INRUD core drug use indicators were used to assess the patterns of drug use. Results. The average number of drugs per prescription was 2.9 (SD 0.5) (recommended: 1.6-1.8), and the percentage of drugs prescribed by generic names was 27.7% (recommended: 100%); the percentage of prescriptions with an antibiotic was 84.8% (recommended: 20.0-26.8%), and with an injection prescribed was 24.9% (recommended: 13.4-24.1%). The percentage of prescribed drugs from the Kenya Essential Medicines List was 96.7% (recommended: 100%). The average consultation time was 4.1 min (SD 1.7) (recommended: ≥10 min), the average dispensing time was 131.5 sec (SD 41.5) (recommended: ≥90 sec), the percentage of drugs actually dispensed was 76.3% (recommended: 100%), the percentage of drugs adequately labeled was 22.6% (recommended: 100%), and the percentage of patients with correct knowledge of dispensed drugs was 54.7% (recommended: 100%). Only 20% of the PPHCCs had a copy of KEML available, and 80% of the selected essential drugs assessed were available. Conclusion. The survey shows irrational drug use practices, particularly polypharmacy, nongeneric prescribing, overuse of antibiotics, short consultation time, and inadequacy of drug labeling. Effective programs and activities promoting the rational use of drugs are the key interventions suggested at all the health facilities.